Religious and moral education in Scottish non-denominational primary schools: charting curriculum change through school handbooks - Scholes, Stephen C. (British Journal of religious education, 2025)
Religious and Moral Education (RME) in primary schools has been an under-researched aspect of state-funded schooling in Scotland. It has received little scholarly comment, and even less empirical research has been conducted on the extent and nature of provision since the implementation of Scotland’s Curriculum for Excellence from 2010 onwards. Using the findings from a document analysis of ninety school handbooks from one local education authority, this article contributes to the limited scholarship on this topic. Through a discussion of the themes of compliance, content, and community, the article highlights ongoing challenges concerning implementing CfE RME in the primary sector. It concludes by considering the marginalisation of RME and suggesting that focusing on professional learning and further empirical research are vital next steps.